The Dual in Nonlinear Programming and Its Economic Interpretation - Balinski, M. L.; Baumol, W. J. (Review of Economic Studies, 1968)
M. L. Balinski, W. J. Baumol; The Dual in Nonlinear Programming and its Economic Interpretation1, The Review of Economic Studies, Volume 35, Issue 3, 1 Jul